2017
DOI: 10.1590/1413-785220172501166234
|View full text |Cite
|
Sign up to set email alerts
|

Bimalleolar Ankle Fracture: A Simple Fracture?

Abstract: Objective: To evaluate the frequency of deltoid ligament injury in bimalleolar supination-external rotation type fractures and whether there is a correlation between the size of the fractured medial malleolus and deltoid ligament injury . Methods: Twenty six consecutive patients underwent magnetic resonance exams after clinical and radiographic diagnosis of bimalleolar supination-external rotation type ankle fractures . Results: Thirteen patients (50%) presented deltoid ligament injury associated to bimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…They reported that the deltoid ligament was injured in 50% of cases with SER bimalleolar fractures, and there was a relationship between small fragments associated with anterior colliculus and deltoid ligament injury. There was no difference in the size of fragment between the medial malleolar fractures with fully ruptured deltoid and those with intact deltoid [8]. However, in this study, the evaluation was made only based on MR findings.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…They reported that the deltoid ligament was injured in 50% of cases with SER bimalleolar fractures, and there was a relationship between small fragments associated with anterior colliculus and deltoid ligament injury. There was no difference in the size of fragment between the medial malleolar fractures with fully ruptured deltoid and those with intact deltoid [8]. However, in this study, the evaluation was made only based on MR findings.…”
Section: Discussionmentioning
confidence: 71%
“…However, these studies suggested that the deltoid ligament is not damaged in fractures of the supracollicular region. Even, this injury was associated with anterior collicular fractures [7,8]. Bozscyk et al [9] suggested that many fibular fractures traditionally recognized as supination injuries actually can be caused by a pronation mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations